Impact of Obesity on Outcomes of Operable Breast Cancer: A Retrospective Cohort Study - Tanapat Engkakul (2020)
OBJECTIVE: Obesity is increasing worldwide. Previous studies of the impact of obesity on breast cancer outcomes have reported conflicting results. We investigated the association of obesity and breast cancer survival in Thai patients. METHODS: Medical records of operable breast cancer patients diagnosed and treated at Siriraj Hospital between January 2004 and December 2011 were reviewed. Demographic data, tumor characteristics, stage, treatment and adverse event were described. Obesity was defined as body mass index (BMI) ≥ 25 kg/m2 using Asian's cutoff value.  Survivals in both obese and non-obese patient groups were analyzed. RESULTS: A total of 400 patients were included, 200 in each group. Obese patients were older and associated with more comorbidity. Obesity was associated with larger tumor size (p = 0.011), greater numbers of lymph node involvement (p = 0.003) and more advanced stage (p = 0.01). Obese patients were more likely to receive less adjuvant chemotherapy and hormonal treatment. There was no statistically significant difference in disease-free survival (DFS) (Hazard ratio [HR] 0.72, 95% confidence interval [CI] 0.46 to 1.13) and overall survival (OS) (HR 0.77, 95% CI 0.43 to 1.39) between obese and non-obese patients. Interestingly, obesity was associated with fewer complications from chemotherapy than non-obese patients (p = 0.047). CONCLUSION: Obesity had no adverse prognostic impact association on both DFS and OS in Thai patients with operable breast cancer, although obese patients more often presented with larger tumor and higher numbers of lymph node involvement. .